A Study on the production system of Lovecraft Garments - Mole, Ma. Amparo; Mendoza, Ma. Lourdes Cecilia A.; dela Cruz, Michael Francis A.; Bulahan, Kenneth John M.; Banaad, Jose Carlos N. (Diliman, Quezon City College of Engineering, 1986)
Lovecraft Garments is a single proprietorship business firm established in 1977 and is registered with the government and the National Cottage Industries Development Authority (NACIDA). With about fifteen (15) people involved in the actual operations, this medium scale industry specializes in the manufacture of high quality garment products, particularly roundneck t-shirts, shirts with collar, night gowns, pajamas, shorts, underwear, dresses, blouses and baby clothes. Due to the limited resources, especially in terms of its labor force/manpower, the General Manager is the one directly in charge of the functions of Marketing, Finance, and Research and development. The General Manager also supervises an assistant General Manager, who takes charge of the functions of Production and Administrative work. Lovecraft Garments is basically a job-order type of production system. The production process starts when the designer is able to create new designs for the approval of the management. Once these designs are approved, they are presented to different clients (particularly large department stores). Purchase Orders (P.O.'s) from these clients now come in (if they conform to the designs sent by Lovecraft Garments). The management will first decide whether they will be able to meet these demands of these different clients (especially when they come in all at the same time) before finally scheduling a certain job (based on a certain purchase order). The criteria for this decision are the capacity of the plant (in terms of man power and machines available) and on the deadline (delivery date) set by the clients and also on the availability of raw materials. The actual production processes will commence once a certain job has been scheduled by the management. This starts with the cutting instructions as per quantity, schedule, materials to be used and deadline (date). The cut materials then undergo quality inspection, to check the sizes, if there are any damages or if the quantity of cut materials tallies with the requirements for that job. When printing and/or embroidering is necessary, there will be a corresponding delay of around two (2) weeks before the (subcontracted) printer and/or embroiderer can deliver back these cut materials. Upon delivery back from the printer and/or embroiderer, the production coordinator will first conduct a quality inspection on the job done by the printer and/or embroiderer. once a receipt is finally accomplished, the actual sewing will, then commence, depending on the type of product and the corresponding style. Once finished, a quality check is a gain conducted to see if there are any defects and if the number of finished goods tallies with the number of cut materials provided for the certain job. These checked finished goods will pass through the Cleaning and Packaging Section (for self-explanatory procedures). While packing, the finished goods are sorted according to size, color, quantity, etc. The stock clerk keeps a record of these finished goods, so that when everything else is in order (as far as quality and quantity is concerned), the secretary can now prepare a sales invoice and delivery receipt for the actual delivery to the customers. A job lot protection system in itself is a limitation. There are certain problems that arise from not being able to predict the trend of the demand for the coming time periods. Without a forecasted demand, there is no proper inventory control especially since the management does not determine quite well which raw materials will really be needed for these coming periods. Without a forecasted demand, the management cannot really make the proper production schedule which will maximize the use of the machines and available manpower. Being in a situation like this, one would not really know what to expect. These problems arising from the fact that Lovecraft is a job order type of production system are further worsened by the inefficiency of the workers. There are cases wherein the workers (particularly the cutters and the sewers) cannot follow to the very detail the instructions given to them, even though some of these instructions are written down on certain forms.
For its part, the group has tried to analyze the main causes of these problem areas and their resulting effects. An evaluation of the things that are needed to be done to solve the problems was presented. Different recommendations were presented, based on what the group felt was the most efficient way of tackling the problem. Included in these recommendations are methods of trying the forecast the demand for the coming time periods, which in turn will be useful in production scheduling and the proper inventory control. There is also the recommendation to improve certain forms, to make them clearer and more self explanatory, for the benefit of the insufficiently educated workers. In line with these production schedules are recommend forms, the group found a need to make use of a route sheet and some sort of a product manual, wherein the different steps involved in the manufacture of that certain product are outlined (making use of the route sheet again), and an outline process chart and similar charts and diagrams are presented. This product manual can serve as training ground for workers, to make them know of what to do should a product of a similar type needs to be produced in the coming periods. A cost analysis of hiring a supervisor to look into and guide the workers (to minimize their mistakes) is also presented at the end. As a final word, the group wishes to inform the readers that certain underlying assumptions had to be made the analysis quite simpler.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Lovecraft Garments; Clothing trade; Production engineering